AN EMPIRICAL STUDY ON RISK AND OPPORTUNITIES OF USE OF ARTIFICIAL INTELLIGENCE IN THE INDIAN INSURANCE SECTOR - Pallathadka, Harikumar; Kirana Pallathadka, Laxmi (International Journal of Psychosocial Rehabilitation, 2021)
Studies have been done to understand the use cases of AI or Artificial intelligence, in the insurance sector. Specifically, they aim to explore the scope and market penetration of Artificial Intelligence in the insurance sector to overcome ongoing issues for better consumer satisfaction. Based on the concept of Artificial Intelligence, the conceptual model has been developed. This conceptual model mainly aims at measuring the relation between Artificial Intelligence and its use case in the insurance sector. These studies conclude specific practical insights that are considered helpful for the insurance companies while responding to the dissatisfied consumers and the other operational issues Previously, the party to the insurance contract, the insurer and insured, used to have different information. It is crucial for understanding the insurance economies as asymmetry causes strategic behavior. The insurer tries to get maximum data so that the behavior of the insured may be inferred.